HAM dalam Wacana: Pro-Kontra dari Masa ke Masa - HS Brodjo Sudjono (Jurnal Hukum IUS QUIA IUSTUM, 2003)
Human rights history and development experiencing many descends and ascends. This phenomenon can not expelled from social and political conditon at that moment. In this modem era, human rights is entering third generation, where human rights no longer viewed merely from political, economy, social and vulture perspective, ut more as universal solidarity rights even thought in reality this third generation still retain numerous problems.